Democracy and the state in the new Southern Europe - Gunther, Richard; Diamandouros, Nikiforos P.; Sōtēropoulos, Dēmētrēs A., 1960- (Oxford studies in democratization., 2006)
Analysing the evolution of selected public policies and the changing roles and structure of the state in Greece, Italy, Portugal, and Spain since the 1960s, this volume makes a major contribution to work on democratic regime transition in southern Europe.